Knowledge Levels of Generation Z on Aceh Community's Local Wisdom in Disaster Mitigation - Gadeng, Ahmad Nubli; Desfandi, Mirza; Ridha, Syahrul; Ruliani, Ruliani; Shafida, Maya (TDMRC, Universitas Syiah Kuala, 2024)
The aim of this study is to determine the knowledge level of Generation Z regarding the local wisdom of the Aceh community in disaster mitigation. A descriptive quantitative method was used, with students from Syiah Kuala University representing Generation Z as the sample. Data were collected using a true/false test administered to the students. The data were then analyzed using statistical formulas, with knowledge levels classified into high, medium, and low categories. The results showed that, for each aspect of Acehs local wisdom in disaster mitigation, the students' knowledge level was below 20% (58 respondents). Out of a total of 288 respondents, only 17% (49 students) exhibited a high level of knowledge, 19% (55 students) a low level, and 64% (184 students) a medium level regarding the local wisdom of the Aceh community for disaster mitigation. In conclusion, the study suggests that Aceh's local wisdom for disaster mitigation may be at risk of fading among future generations. Thus, there is a need for serious efforts from both the government and the Aceh community to socialize and internalize this local wisdom among the younger generation.